Endodontic re-treatment and restorative treatment of a dens invaginatus type II through new technologies - Zubizarreta-Macho, Álvaro (J Clin Exp Dent, 2019)
BACKGROUND: The complex anatomy of dens invaginatus makes access cavity to root canal system difficult, which has an impact on the prognosis of these teeth. A novel technique, based on new technologies, is proposed to make access cavity conservative and guided with minimal dental structure lost. MATERIAL AND METHODS: This case report shows the root canal retreatment and the endodontic surgery of a dens invaginatus type II in a left lateral upper incisor previously treated which was affected by a chronic apical abscess and an apical fracture. A Cone Beam Computed Tomography was performed to better diagnosis the dental anatomy. An intraoral scan was performed to get a digital 3D model. A computer-guided implant planning software was used to plan the access cavity and design the splint guided. Finally, the clinical crown was restored by a resin nanoceramic veneer made by a chairside system made up of an intraoral scanning unit and a grinding unit. Last, the authors carried through the endodontic surgery to extract the apical fractured fragment. RESULTS: Follow-up appointments at 6, 12 and 18 months showed a radiographic reduction of the periapical lesion and absence of clinical signs. CONCLUSIONS: The splint guide allowed a guided and conservative access cavity to root canal system. It facilitates the root canal retreatment and improves the prognosis of the teeth with dental malformations. Key words:CAD-CAM, Cone-Beam Computed Tomography, dens in dente, dens invaginatus, dental pulp cavity, endodontics.